2018
DOI: 10.1159/000486648
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the New Kidney Allocation System among United States Dialysis Providers with Low Waitlisting

Abstract: It is unknown whether dialysis facility staff are aware of the new kidney allocation system implemented in December 2014, which changed how deceased donor kidneys are allocated and waiting time is calculated. U.S. dialysis facilities with low annual waitlisting (<15.2%) were surveyed as part of a large randomized study. Among 653 facilities, 57.9% of staff were aware of the policy change, with medical directors (84.4%) being more aware than social workers (73.3%), facility administrators (53.1%), nurse manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…With the Advancing American Kidney Health initiative and broad CMS-mandated quality improvement goals, there has been increased national attention on expanding access to kidney transplantation, and dialysis units are tasked with helping patients obtain transplants. 8 , 9 Achieving these goals requires that we leverage both dialysis and transplant professionals’ expertise to improve patient outcomes. Further research, particularly patient-centered outcomes research, is needed on how dialysis and transplant staff can facilitate patients’ access to kidney transplants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the Advancing American Kidney Health initiative and broad CMS-mandated quality improvement goals, there has been increased national attention on expanding access to kidney transplantation, and dialysis units are tasked with helping patients obtain transplants. 8 , 9 Achieving these goals requires that we leverage both dialysis and transplant professionals’ expertise to improve patient outcomes. Further research, particularly patient-centered outcomes research, is needed on how dialysis and transplant staff can facilitate patients’ access to kidney transplants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of dialysis unit staff highlighted opportunities for improved practices, such as using evidence-based patient education strategies. 3 , 5 , 9 , 10 , 11 Our study builds on previous research with dialysis unit staff and, to our knowledge, is the first to also examine transplant center staff perspectives on patient-level barriers to transplantation in the United States.…”
mentioning
confidence: 99%
“…This is especially true given that we found that patients most often turned to their physicians for information when choosing centers, but prior studies have shown that healthcare providers have limited awareness of the allocation system or of disparities in kidney transplantation. 24,25 Disparities in patient education about transplant have direct effects on access to transplantation, and prior studies have found that patient education has the ability to reduce racial and socioeconomic disparities in completion of transplant evaluation. 11,26 Furthermore, prior studies have found that patients with lower education attainment were more likely to report psychosocial concerns regarding pursuing transplantation, and less likely to believe transplantation would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…( 27 ) While longer term outcomes are still being examined for this study, the interim outcome of dialysis provider knowledge about KAS was significantly improved three months after baseline among the intervention vs. control group ( 28 ). Among 655 U.S. dialysis facilities with low waitlisting nationwide included in ASCENT, baseline data showed that only 57.9% of dialysis facility staff were aware of the KAS change ( 29 ) and only 19% of staff were aware there was a racial disparity in waitlisting ( 29 ). After 3 months, knowledge scores among dialysis providers in the intervention were higher (mean difference in knowledge: 0.25 (95% confidence interval CI, 0.11-0.48; P = 0.039) compared to nonintervention providers, suggesting that dialysis facility provider education may extend the impact of a national policy change in kidney allocation and disparity reduction ( 28 ).…”
Section: Collaborative Sektx Coalition Projects Aimed At Increasing A...mentioning
confidence: 99%